Generation of flow and droplets with an ultra-long-range linear concentration gradient. Issue 22 (27th October 2021) - Dai, Bo; Long, Yan; Wu, Jiandong; Huang, Shaoqi; Zhao, Yuan; Zheng, Lulu; Tao, Chunxian; Guo, Shiwei; Lin, Francis; Fu, Yongfeng; Zhang, Dawei; Zhuang, Songlin
Abstract : A concentration gradient generator is demonstrated to generate ultra-long linear gradients, periodic gradients and droplets with various concentrations and produce drugs with different concentrations for drug screening applications. Abstract : In the chemical and biological fields, the creation of concentration gradient microenvironments is an important approach for many applications, such as crystal growth and drug screening. Although many concentration gradient generators have been demonstrated, current generators can hardly produce ultra-long linear concentration gradients. In this paper, we propose a concentration-gradient flow/droplet generator which consists of a microfluidic flow switch, a cavity array for stage-by-stage concentration dilution, and an optional T-junction for droplet formation. The generator can realize an ultra-long continuously-varying concentration gradient along the flow direction. Generation of a 38 mm concentration gradient was demonstrated. The length can be further extended by enlarging the capacity of the cavities and increasing the number of the stages. The concentration gradient showed high linearity in the range of 10% to 90%. Moreover, cyclic generation of a concentration gradient flow and droplets with different concentrations was realized by the generator. In a demonstration of drug screening, the generator was employed to produce paclitaxel in different concentrations. A negative correlation between the 4T1 cell viability and the paclitaxel concentration was observed after the treatment. We envision that the concentration gradient generator will be a promising candidate for various drug screening applications.